2020 CAO Clinical Practice Guideline: Optometric Low Vision Rehabilitation FULL GUIDELINES - Leat, Susan (Canadian Journal of Optometry, 2020)
The purpose of the Low Vision Clinical Practice Guideline for Canadian Optometrists is to assist them in providing the best level of care in the management of patients with low vision. The guideline is based on current best evidence regarding optometric low vision rehabilitation as interpreted by an expert panel. The writing group includes optometrists from academia and private practice, representing various regions across Canada. This guideline will aid optometrists in identifying patients who require low vision rehabilitation and recommends appropriate assessment and management. As primary eye care providers, optometrists are optimally trained and qualified to identify and manage patients who would benefit from low vision rehabilitation. Optometrists, based on their geographical presence in local communities, are also well positioned to provide initial rehabilitation in a timely, effective manner, and to initiate referral for more comprehensive rehabilitation if required.